Biopriming salt-tolerant microbial isolates to chilli and pak choy seeds: a study on salinity tolerance and physiological responses of treated seeds - Chin, Jia May; Ting, Adeline Su Yien (Acta Biologica Szegediensis, 2023)
Trichoderma asperellum and Pseudomonas fluorescens were first established for their tolerance to salinity. They were bioprimed onto two common vegetable seeds (pak choy and chilli) using sodium alginate (for T. asperellum, TAB) and xanthan gum (for P. fluorescens, PFB) and sown into soils amended with NaCl (salinity stress). Both T. asperellum and P. fluorescens have high salt tolerance (up to 250 mM of NaCl) concentration). Bioprimed seedlings had sustained growth in saline soils (2.72 – 3.05 dS/m). Pak choy seedlings benefited the most from biopriming with TAB or PFB seedlings, showing enhanced fresh weight, shoot length, root length and germination, compared to non-bioprimed seedlings. For chilli seedlings, only shoot length was enhanced. Tolerance to salinity was marked by lower levels of proline (0.62-2.73 µmol/g fr. wt.), total phenolic content (80.29-130.10 mg GAE/100 g fr. wt.), and malondialdehyde (0.29-0.61 µmol/g fr. wt.) compared to non-bioprimed seedlings (NB) under salinity stress (1.87-3.55 µmol/g fr. wt. for proline, 105.60-278.82 mg GAE/100 g fr. wt. for total phenolic content, 0.33-0.61 µmol/g fr. wt. for malondialdehyde). Our early observations showed the potential of biopriming salt-tolerant isolates to enhance survival of important vegetable crops in saline soils.